Student Identify and the First-Year Learning Community - Eiselein, Gregory; Priest, Kerry; Saucier, Donald; Brack, Jenna; Lehning, Emily (Kansas State University. K-State First., 2013)
How does a student's sense of identity impact his or her desire to participate in a learning community? Using research on the Kansas State University CAT Community program, this session examines how attention to student identity formation, including a student's desire for belonging, impacts the short-term and long-term success of learning communities. The session includes practical advice on how to consider identity formation in your strategic planning, instructional design, marketing efforts, and advising process.
Keywords: Assessments; Learning communities; Living-learning communities; Faculty development; Presentations (communicative events)